An Analytical Study of Working Capital Management of Selected Cement Companies in India - Abdulkareem, Ahmed Mahdi; Chakrawal, Alok Kumar (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
This article is to analyze and evaluate working capital management of selected cement companies. The main purpose of this study is to find out the liquidity position of selected cement companies in India, five companies were selection .The duration of study is five years start from 2015-16 to 2019-20. Two ratios were used for the analysis of data: current ratio quick ratio. To test hypothesis ANOVA was used. The major findings of the study indicate that there are significance difference in the quick ratio and current ratio of selected cement companies. Based on the data analysis, there is a mixed trend in the current ratio during the year 2015-16 to 2019-20. The analysis also shows the ups and down in the quick ratio of the selected cements companies during the period of 5 year. It indicates that there is mixed trend in quick ratio during the year 2015-16 to 2019-20. Removing short-term debt from balance sheet allow companies to have better quick and current ratios and allow to save some of liquidity in the near term and put in to better use. Companies are suggested to adopt more aggressiveness in maintaining their current rasio.